ON THE ANTIQUITY OF SERBIAN IDENTITY IN KOSOVO AND METOHIJA - Suljagic, Sanja (Political Review, 2023)
In this text author used an analytical-synthetic method to present directions for proving the source of Serbian identity on the territory of Kosovo and Metohija or „Old Serbia”, as was the name of this territory in the past. The author presented various sources to prove the antiquity of the Serbian Patriarchy of Pec and the formation of the territory of Kosovo and Metohija as a medieval center of statehood and spirituality of Serbian people. This medieval state with its own church jurisdiction, laws, moral values, economic achievements, national customs and manners, and other achievements continued and upgraded the previous church jurisdiction and cultural tradition of Prima Iustiniana. In the text, there is also underlined the significance of the territory of Kosovo and Metohija for Serbian identity in the historical and geopolitical context of genealogical, political, and cultural liaisons of members of the medieval Serbian Nemanjic dynasty with the members of the medieval Greek, Bulgarian, and Russian dynasties. For the purpose of argumentation of significant determinants of the territory of Kosovo and Metohija for Serbian identity, there are used various Serbian and world-historical sources such as the results of archeological research, Serbian medieval state documents, artifacts, heraldic and folk legends and beliefs in the context of historical processes which have shaped the Serbian identity and promoted the territory of Kosovo and Metohija as the cradle of Serbian identity throughout history.
Keywords: Serbs Tribals; Patriarchy of Pec; Nemanjic dynasty; Charters of the Dečani Monastery; Old Serbia; Kosovo and Metohija